PEMANFAATAN BIOPELET SEBAGAI ENERGI TERBARUKAN RAMAH LINGKUNGAN UNTUK KESEJAHTERAAN MASYARAKAT DESA URENG - Mustamu, Sofia; Parera, Lydia R (Jurnal Abdi Insani, 2025)
Fuel is one of the important factors in household industries. However, in recent years, there has been an energy crisis, leading to fuel shortages. The government's effort to address this issue is by utilizing biomass waste to produce bio-pellets, which are environmentally friendly fuels. The community of Ureng village is closely connected to forest products, but they have not yet been able to utilize forest resources optimally. Therefore, the aim of this activity is to introduce and socialize bio-pellets made from biomass waste of the mixed sawdust. The method used in this activity includes raising awareness about the benefits of bio-pellets and providing a simulation on how to produce bio-pellets. The results achieved were the success of the activity, shown by the increase in the village community’s knowledge about the benefits of bio-pellets, with pre-test and post-test scores of 20% and 80%, respectively. Additionally, the community showed great enthusiasm for bio-pellet production, which is expected to reduce the use of fossil energy, decrease biomass waste, and increase village income.